(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional and radiological outcome of Ganz osteotomy for the treatment of acetabular dysplasia (AD) in adolescent and young adults. Methods: This descriptive study was conducted in Department of Orthopaedics and Traumatology Alt?nbas University Medical Faculty Istanbul Turkey from 2nd February 2013 to 2nd January 2022.All adolescent and young adults with acetabular dysplasia(AD) fulfilling the inclusion criteria were operated with Ganz osteotomy(Bernese).Post operative functional results were assesses with Merle d’Aubigne Hip Score and gradded as excellent(score 15-17) good(12-14,average(11-13) and poor(<11).The radiologoical outcome was evaluated in terms of measuring the restoration of Lateral Central-Edge Angle (LCE), Anterior Central-Edge angle (ACE), Acetabuler Index(AI), Lateralized hip sign(LHS) and Shenton-Menard line (SML). Results: We operated on 19 hips in 18 patients.The mean age was 23.05±2.48 years(range 15 to 32 years). Female patients were 13(72.22%) and male 5(27.22%).Left sided Ganz osteotomy was performed in in 9 (50%) patients, right in 8 (44.44%) and both sides in 1 (5.55%) patient. The average follow up peroid was 3.26±6.8 years. All the patients had excellent functional outcome with Merle d’Aubigne Score improved from pre operative 12.47 ± 1.02 to 17.21 ± 1.03 post operative(P<0.05) All the radiological parameters were restored with post operative LCE 35.16 ± 9.25°,ACE 32.37 ± 6.49°,AI 9.16 ± 4.26°,LHS10.00 ± 3.11 mm and intact SML in 13(68.42%) hips.(P<0.05) Conclusion: Ganz osteotomy is an effective technique for the surgical treatment of acetabular dysplasia in adolescents and young adults as shown by excellent functional and radiological outcome in our series.